2014
DOI: 10.1186/1471-2377-14-41
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of novel inflammatory markers in stroke-induced immunosuppression

Abstract: BackgroundAcute ischemic stroke (AIS) has a biphasic effect on the peripheral immune system. The initial inflammatory response is followed by systemic immunosuppression, referred to as stroke-induced immunosuppression (SIIS), leading to severe complications in stroke patients. We aimed to identify an inflammatory marker that best represents this biphasic immunological response after AIS.MethodsWe investigated the alteration of CRP, WBC, neutrophil count, suPAR levels, CD4+ CD25high Tregs, CD64+ and CD177+ neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
(29 reference statements)
1
10
1
2
Order By: Relevance
“…These include: (1) reduced monocytic HLA-DR expression and low CD4 + T-cell counts ( 153 , 154 ), (2) reduced ex vivo TNF-α release by monocytes ( 155 ), and (3) elevated plasma IL-10 levels ( 156 ). In addition, it has recently been postulated that a rise in the frequency of circulating CD64 + neutrophils 1 week after stroke may serve as a marker by which to identify an inflammatory response developing as a consequence of infection ( 157 ). In the context of TBI-induced immune suppression, no study to our knowledge has examined whether alterations in neutrophil surface phenotype can predict the development of infection, a reflection of the paucity of data in this area of research.…”
Section: Tbi and Peripheral Immune Suppression – Unanswered Questionsmentioning
confidence: 99%
“…These include: (1) reduced monocytic HLA-DR expression and low CD4 + T-cell counts ( 153 , 154 ), (2) reduced ex vivo TNF-α release by monocytes ( 155 ), and (3) elevated plasma IL-10 levels ( 156 ). In addition, it has recently been postulated that a rise in the frequency of circulating CD64 + neutrophils 1 week after stroke may serve as a marker by which to identify an inflammatory response developing as a consequence of infection ( 157 ). In the context of TBI-induced immune suppression, no study to our knowledge has examined whether alterations in neutrophil surface phenotype can predict the development of infection, a reflection of the paucity of data in this area of research.…”
Section: Tbi and Peripheral Immune Suppression – Unanswered Questionsmentioning
confidence: 99%
“…White blood cell count or neutrophil count is still indicators of infection and clinical judgment; however, their specificity might not be high (Folyovich et al., 2014; Westendorp, Nederkoorn, Vermeij, Dijkgraaf, & van de Beek, 2011). Surgical drainage and antibiotics are also the effective therapy to treat intracranial infection (Dashti et al., 2008; Kural et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, their specificity might not be high. Studies have shown that blood leukocyte and neutrophil counts after acute stroke are similar in patients with and without infection ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%